A yellow chlorophyll catabolite in leaves of Urtica dioica L.: An overlooked phytochemical that contributes to health benefits of stinging nettle. (15th October 2021) - Karg, Cornelia A.; Doppler, Christian; Schilling, Charlotte; Jakobs, Franziska; Dal Colle, Marlene C.S.; Frey, Nadine; Bernhard, David; Vollmar, Angelika M.; Moser, Simone
Graphical abstract: Highlights: A late stage chlorophyll catabolite was identified and characterized for the first time in fresh Urtica dioica leaves and in nettle tea. Quantification of this catabolite ( Ud -PxB) revealed an amount of up to 100 µg in one cup of nettle tea, with quantities varying largely among different suppliers. Ud -PxB was shown to possess antioxidative and anti-inflammatory properties comparable to known nettle phytochemicals. Chemical and digestive stability was demonstrated for this overlooked phytochemical in nettle leaves Abstract: Stinging nettle is appreciated for its antioxidant and anti-inflammatory properties, which renders the plant a popular ingredient in a healthy diet in form of salads or smoothies. The most common use, presumably, is of dried leaves as ingredient in tea mixtures. The plant's health benefits are attributed primarily to phenolic phytochemicals. Here we describe the characterization and quantification of a phylloxanthobilin (PxB), a yellow chlorophyll catabolite, in nettle tea. Despite their abundance in the plant kingdom, chlorophyll catabolites have been overlooked as phytochemicals and as part of human nutrition. Our investigations of tea reveal that one cup of nettle tea contains about 50 µg of PxB with large variations depending on the supplier. When investigating the bioactivities of PxB, our observations show that PxB has antioxidative and anti-inflammatory activities comparable to known bioactive small molecules found in nettle, indicating the phylloxanthobilin to be an overlooked ingredient of nettle tea.